Pengembangan modul memasuki perguruan tinggi menggunakan pendekatan trait and factor - Puspita, Renny; Daharnis, Daharnis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Basically the goal of career theory is for individuals to have a happy career. Student careers can be said to be solid if they have plans related to self-understanding, environmental understanding, formulation of choices, and formulation of action plans through plans for further education. In fact, high school (SMA) students have not been able to plan and have problems related to careers. High school students' knowledge about the world of higher education is still low. Through the career guidance module, students are expected to be able to prepare and strengthen their career orientation. This research aims to produce a product in the form of a module to enter higher education using a valid, practical and effective Trait and Factor approach. The research method used is development research by following the ADDIE (Analyze, Design, Development, Implementation and Evaluation) model development steps. The research trial subjects consisted of 3 experts to test the validity of the module, 3 counseling teachers/counselors to test the practicality of the module and 35 students to test the effectiveness of the module. Research data were analyzed using descriptive analysis and nonparametric statistics. The results of the study show that: (1) the module entering college using the Trait and Factor approach is in the valid category, (2) the practical level of the module entering college using the Trait and Factor approach developed is in the very high category for use by guidance counselors/counselors and students, (3) the module for entering college uses an effective Trait and Factor approach to improve students' ability to analyze universities. Thus, the modules developed are valid, practical and effective and can be used by guidance counselors/counselors to improve students' abilities in analyzing the college they will enter.